anonymous
  • anonymous
solve by completing the square.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
x\[x ^{2}+2x=24\]
anonymous
  • anonymous
move all one side you get\[x^{2} +2x -24 =0\]
anonymous
  • anonymous
now you factour(x+6)(x-4)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
x=-6 x=4
anonymous
  • anonymous
\[2x ^{2}-4x-3=0\]
anonymous
  • anonymous
this is quadratic equation form: [-b±√(b^2-4(a)(c))]/(2(a)) a=2 b=-4 c=-3 [-(-4)±√((-4)^2-(4*2*(-3))]/(2*2)) [(4)±√(16+24)]/(4) [(4)±2√(10)]/(4) x =1/2[±√(10)]
anonymous
  • anonymous
The above method is not "completing the square"
anonymous
  • anonymous
annette the second you want do complete square?
anonymous
  • anonymous
Even in first one, it is splitting the middle term method and not completing the square
anonymous
  • anonymous
Thank you Harkirat for remind me let do again , can you do second one it late I have to go 2/2=1 , 1^2 =1 (x+1)^2=24+1 (x+1)^2=25 x +1 = √(25) x = -1± 5 x=-6 or x= 4
anonymous
  • anonymous
For the second we proceed as follows: \[2x ^{2}-4x-3=0\]
anonymous
  • anonymous
First we take -3 to RHS as 3\[2x ^{2}-4x=3\]
anonymous
  • anonymous
Next we divide both sides by 2 (to get rid of the 2 in front of x^2) So we get \[x ^{2}-2x=3/2\]
anonymous
  • anonymous
Now to complete the square we add 1^2 to both sides \[x ^{2}-2x+1^{2}=3/2 + 1\]
anonymous
  • anonymous
Now left side is a complete square as follows \[(x-1)^{2}= 5/2\] This gives \[x-1 = \pm \sqrt{5/2}\] Now taking -1 to RHS we get the final answer \[x = 1 \pm \sqrt{5/2}\]
anonymous
  • anonymous
So the two roots/zeros of the given quadratic equation are \[1+\sqrt{5/2}\] and \[1-\sqrt{5/2}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.